SAT0097 Effective Control of Rheumatoid Arthritis Disease Activity Prevents Development or Acceleration of Subclinical Atherosclerosis over 3 Years. (15th July 2016) - Arida, A.; Protogerou, A.D.; Konstantonis, G.; Fragkiadaki, K.; Kitas, G.D.; Sfikakis, P.P.
Abstract : Background: Rheumatoid arthritis (RA) associates with increased cardiovascular disease (CVD) morbidity and mortality due to accelerated atherosclerosis, attributed to both classical risk factors and chronic inflammation. Objectives: To examine whether effective inflammation control prevents development and/or modifies acceleration of subclinical atherosclerosis in RA. Methods: Consecutive, non-diabetic RA patients (n=139), aged 61.3 (52.9–67.9) years, with RA duration 10 (5–17) years, followed-up at least every 4 months in our center and previously examined by ultrasonography for subclinical atherosclerosis, were prospectively re-evaluated after 3.2 (3.1–3.3) years. None had known CVD, malignancy, chronic renal failure, or other chronic or acute inflammatory disease at baseline. The only inclusion criterion in the prospective study was effective disease control during the follow-up period, determined arbitrarily as the presence of remission or of low disease activity (DAS28<3.2) for at least 75% of this period. Non-diabetic control individuals without CVD at baseline (n=251, aged 56.1 (44.9–56.1) years) were studied in parallel (median follow-up of 3.2 (3.1–3.3) years). Preclinical atherosclerosis was assessed as described in detail elsewhere [1, 2]. Results: Formation of new atheromatic plaques in carotid and femoral arterial beds, reflecting atheromatosis, was evident in 22% of RA patients versus 28% of controls. Carotid intima-media thickness, reflecting arterial wall hypertrophy, increased per year by 0.010 (0.002–0.023) in RA versus 0.011 (0.002–0.023) in controls for the left common carotid artery and by 0.010 (0.002–0.023) in RA versus 0.011 (0.000–0.025) for the right common carotid artery. Pulse wave velocity, reflecting arterial stiffness, changed per year by 0.071 (-0.149- 0.275) in RA versus -0.015 (-0.247–0.184) in controls. Two of 139 patients versus 1 of 251 controls developed clinical CVD during follow-up. By multivariate analysis after correcting for age, gender, smoking, body mass index, hypertension, hyperlipidemia, as well as anti-hypertensive and lipid lowering therapies, no statistically significant differences for any of the evaluated markers of subclinical atherosclerosis were found between patients and controls. Conclusions: Effective inflammation control seems to abrogate any RA-specific effect on the progression of atherosclerosis. Whether early and sustained disease control translates to the expected for the general population rates of cardiovascular morbidity and mortality in RA patients remains to be proven by large prospective cohort studies. References: Arida A, Zampeli E, Konstantonis G, et al. Rheumatoid arthritis is sufficient to cause atheromatosis but not arterial stiffness or hypertrophy in the absence of classical cardiovascular risk factors. ClinRheumatol. 2015:34(5):853–9. Zampeli E, Protogerou A, Stamatelopoulos K, et al. Predictors of new atherosclerotic carotid plaque development in patients with rheumatoid arthritis: a longitudinal study. Arthritis Res Ther. 2012:14(2):R44 Disclosure of Interest: None declared